2001
DOI: 10.1016/s0735-1097(00)01204-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-time perfusion imaging with low mechanical index pulse inversion Doppler imaging

Abstract: Pulse inversion Doppler imaging allows the detection of myocardial perfusion abnormalities in real-time during stress echocardiography and will further add to the quality and sensitivity of this test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 11 publications
3
96
0
10
Order By: Relevance
“…[5][6][7] Low-MI imaging is less technically demanding than triggered imaging and enables simultaneous assessment of myocardial perfusion and wall motion in real time. 8 For both high-and low-MI MCE imaging, vasodilators are the most feasible stressors, [5][6][7] but these agents do not reliably provoke inducible WMAs. 9 Conversely, exercise is the preferred stress in active patients but has proven technically challenging for MCE because of immediate postexercise hyperventilation, cardiac translational motion, and the relatively short duration of hyperemia.…”
mentioning
confidence: 99%
“…[5][6][7] Low-MI imaging is less technically demanding than triggered imaging and enables simultaneous assessment of myocardial perfusion and wall motion in real time. 8 For both high-and low-MI MCE imaging, vasodilators are the most feasible stressors, [5][6][7] but these agents do not reliably provoke inducible WMAs. 9 Conversely, exercise is the preferred stress in active patients but has proven technically challenging for MCE because of immediate postexercise hyperventilation, cardiac translational motion, and the relatively short duration of hyperemia.…”
mentioning
confidence: 99%
“…In recent years, myocardial contrast echocardiography has been demonstrated to be a feasible and accurate method for the evaluation of myocardial perfusion in many clinical settings (2)(3)(4)(5). In addition, the combination of intravenous contrast agents and RTMCE with application of high-mechanical index impulses for microbubble destruction followed by myocardial replenishment has permitted the quantification of myocardial blood flow (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Microbubbles were prepared by hand shaking 8 mL of decafluorobutane gas with a 3:1 mixture of 5% dextrose and 5% human serum albumin and the mixture was sonicated for 75 s. The mean concentration of microbubbles produced with this technique was 1.4 x 10 9 microbubbles per mL and the mean size was 4.6 ± 0.2 µm (as reported in Ref. 2). RTMCE was obtained by continuous intravenous infusion of 0.2 mL/kg PESDA diluted in 80 mL of normal saline at a rate of 2-3 mL/min, injected through the femoral vein.…”
Section: Myocardial Contrast Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Porter and his colleagues demonstrated that simultaneous assessment of myocardial perfusion and LV wall motion with real time MCE imaging was superior to regional wall motion analysis only during dobutamine stress echocardiography [21]. In 117 patients, among whom 40 patients had QCA, a better agreement between MCE and QCA (83%) was observed than that between wall motion abnormality and QCA (72%).…”
Section: Mce In the Detection Of Coronar Y Arter Y Stenosismentioning
confidence: 99%